Proceedings of the 4th International Conference on Numerical Modelling in Engineering Volume 2: Numerical modelling in Mechanical and Materials Engineering, NME 2021, 24-25 August, Ghent University, Belgium - Abdel Wahab, Magd.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers outstanding papers on numerical modeling in Mechanical Engineering (Volume 2) as part of the 2-volume proceedings of the 4th International Conference on Numerical Modeling in Engineering (NME 2021), which was held in Ghent, Belgium, on 24-25 August 2021. The overall objective of the conference was to bring together international scientists and engineers in academia and industry from fields related to advanced numerical techniques, such as the finite element method (FEM), boundary element method (BEM), isogeometric analysis (IGA), etc., and their applications to a wide range of engineering disciplines. This book addresses numerical simulations of various mechanical and materials engineering industrial applications such as aerospace applications, acoustic analysis, bio-mechanical applications, contact problems and wear, heat transfer analysis, vibration and dynamics, transient analysis, nonlinear analysis, composite materials, polymers, metal alloys, fracture mechanics, fatigue of materials, creep, mechanical behavior, micro-structure, phase transformation, and crystal plasticity.
Aerospace applications -- Biomechanical applications -- Vibration and dynamics -- Composite materials -- Mechanical behaviour.
Keywords: Mechanical engineering; Numerical analysis; Mathematical physics; Mechanical Engineering; Numerical Analysis; Theoretical, Mathematical and Computational Physics; Mechanical engineering -- Mathematical models -- Congresses